Structure-activity relationship studies of 2-phenylbenzimidazoles and related organometallic complexes as antiplasmodial agents - Rylands, Laa-iqa (Department of Chemistry, 2019)
Malaria remains a huge public health concern, affecting millions of people from all around the world. The widespread resistance by Plasmodium parasites to previously effective quinoline-based drugs and the emerging resistance to current antimalarial therapies, stresses the urgent need for the exploration and development of diverse new classes of compounds. Amongst other requirements, these diverse new compound classes should target resistant strains in particular. In this regard, benzimidazoles have been identified as promising potential drug candidates, displaying potent antiplasmodial activity. Furthermore, benzimidazoles can be chemically transformed into metal-containing organometallic complexes that elevate generally flat benzimidazoles to the third dimension. To date, examples of metal-containing benzimidazoles are extremely limited, with only two reported as having antiplasmodial activity. Thus, we report the syntheses of a series of substituted 2-phenylbenzimidazole ligands, from the cyclo-condensation of o-phenylenediamines and benzaldehyde, as well as the synthesis of Ru(II) and Ir(III) cyclometallated benzimidazole complexes. All of the compounds synthesised were fully characterised by 1H and 13C{1H} Nuclear Magnetic Resonance (NMR) Spectroscopy, Elemental Analysis and Mass Spectrometry. The synthesised 2-phenylbenzimidazoles and metal complexes were screened in vitro against the chloroquine-sensitive NF54 strain and selected complexes were screened against the chloroquine-resistant K1 strain of P. falciparum. In addition, selected compounds were also tested against the Chinese Hamster Ovarian (CHO) mammalian cell-line to evaluate their selectivity. The 2-phenylbenzimidazoles generally displayed weak to moderate antiplasmodial activity against the chloroquine-sensitive NF54 strain, where IC50 values ranged from 3.27 – 32.97 µM. Furthermore, it was demonstrated that the antiplasmodial activities of the 2-phenylbenzimidazoles increased significantly upon metal complexation, using Ru and Ir metals. In general, the antiplasmodial activity of the Ru(II) complexes were significantly better compared to the Ir(III) complexes. The cyclometallated benzimidazole complexes were much more active across both parasite strains (0.12 < IC50 < 4.31), compared to the corresponding ligands tested. The unsubstituted Ru(II) and Ir(III) cyclometallated benzimidazole complexes were found to possess the most potent antiplasmodial activity against the NF54 strain, displaying IC50 values of 0.12 and 0.19 µM, respectively. In most cases, the resistance indices obtained for the select compounds tested were significantly lower compared to chloroquine, which suggested that the compounds are not cross-resistant with chloroquine. Furthermore, cytotoxicity studies indicated that the synthesised compounds had low cytotoxicity and were selective towards the malaria parasites. Additional studies which involved testing the aqueous solubility of selected compounds in PBS buffer at pH 6.5 showed that the introduction of water-solubilising groups improved the compounds solubility significantly. Preliminary mechanistic studies suggested that the synthesised benzimidazoles may have a different mode of action to chloroquine as the compounds did not inhibit β-haematin formation at the maximum concentration of 500 µM.